TRADISI RUWATAN MURWAKALA ANAK TUNGGAL DALAM TINJAUAN SOSIOKULTURAL MASYARAKAT JAWA - Setiawan, Eko (P3M IAIN KEDIRI, 2018)
The tradition of ruwatan children as one of the traditional Javanese heritage is still preserved. Ruwatan a purification to overcome or avoid an inner difficulty by way of performing wayang kulit by taking the murwakala or sudamala. The tradition of ruwat anak tunggal is the tradition of throwing away the sengkala or bad luck that existed in a single child. In the process of tradition ruwat usually done first begins with a leather puppet performances. The Ruwatan tradition as part of Javanese customs is a tradition of traditional heritage which is still believed to be a means of disposing of sengkala or bad luck in a single child.